RESPONS TANAMAN KACANG HIJAU (Vigna radiata. L) TERHADAP PEMBERIAN AMELIORAN KATION POLIVALEN Cu2+, Fe3+, Zn2+ DAN KOMPOS PELEPAH KELAPA SAWIT PADA MEDIA GAMBUT - Nursamsul Kustiawan; Siti Zahrah; Maizar; Tati Maharani (DINAMIKA PERTANIAN, 2022)
The purpose of this study was to determine the response of mung bean to the application of ameliorant polyvalent cations Cu2+, Fe3+, Zn2+ and Palm Oil Midrib Compost Fertilizer on Peat Media. The research was carried out in the experimental farm of the Faculty of Agriculture, Riau Islamic University, Pekanbaru from March to May 2020. The design used in this study was a factorial completely randomized design consisting of two factors. The first factor is the provision of ameliorant material (A) consisting of 4 levels of A0 (without ameliorant), A1 (Cu2+), A2 (Fe3+), and A3 (Zn2+) and the second factor is the provision of palm frond compost (K) consisting of 4 levels of K0 ( without compost) K1 (12 g/plant) K2 (24 g/plant) K3 (36 g/plant). Observational data were analyzed statistically and further test BNJ level 5%. The results of the study by interaction gave an influence on the observation of seed weight per plant, with the best treatment being the provision of ameliorant Cu2+ and oil palm midrib compost 24 g/plant (A1K2). The main effect of giving ameliorant material gave effect on all observation parameters, namely plant height, relative growth rate, speed of dry matter filling, effective seed filling time, flowering age, harvest age, seed weight per plant, percentage of empty pods, the weight of 100 seeds and root volume, where the best treatment is in the provision of ameliorant Cu2+ (A1). The main effect of oil palm midrib compost affects the observation parameters, namely plant height, relative growth rate, speed of dry matter filling, flowering age, harvest age, seed weight per plant, percentage of empty pods, weight of 100 seeds and root volume where the best treatment is in giving 24 g/plant (K2) of oil palm midrib compost.